1993
DOI: 10.1016/0014-5793(93)80647-d
|View full text |Cite
|
Sign up to set email alerts
|

Selective interaction of ferricyanide with cluster I of Clostridium pasteurianum 2[Fe4S4] ferredoxin

Abstract: Treatment of Clostridium pasteuriunum ferredoxin (CpFd) with stoichiometric amounts of potassium ferncyanide results in the specific conversion of cluster I into a Fe& species while leaving cluster II unaltered. Ferricyanide-treated CpFd derivative has been purified and characterized through biochemical and spectroscopical techniques. The cluster conversion process is reversible and reconstitution of native CpFd has been afforded under appropriate conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…Deprotonation of such a bulky group as tyrosine is believed to bring about significant conformational variations of the protein around the cluster; we therefore decided to monitor the high pH transition of CpFd by CD spectroscopy, a technique particularly sensitive to conformational rearrangements at the active site of metalloproteins. As reported, the visible CD spectrum of oxidized CpFd is characterized by two intense positive bands, respectively, located at 410 and 565 nm, plus a broad negative band around 700 nm [22,23]. The spectrum is pH independent from pH 7 to 9 (see also [14]).…”
Section: 'H Nmr Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Deprotonation of such a bulky group as tyrosine is believed to bring about significant conformational variations of the protein around the cluster; we therefore decided to monitor the high pH transition of CpFd by CD spectroscopy, a technique particularly sensitive to conformational rearrangements at the active site of metalloproteins. As reported, the visible CD spectrum of oxidized CpFd is characterized by two intense positive bands, respectively, located at 410 and 565 nm, plus a broad negative band around 700 nm [22,23]. The spectrum is pH independent from pH 7 to 9 (see also [14]).…”
Section: 'H Nmr Resultsmentioning
confidence: 55%
“…In particular the sequence-specific assignments of the hyperfine signals permit the observed variations in shape and position of these signals to be correlated with specific perturbations of well-defined portions of the protein [6,12]. For instance, we have investigated the effects of addition of ferricyanide to oxidized ferredoxin and unambiguously shown that cluster I is converted into a Fe,& cluster while the hyperfine signals of cluster II are virtually unaffected [23]. In addition, the paramagnetic 'H NMR spectra of two sitedirected mutants of CpFd, respectively at Pro-19 (P19K) and Pro-48 (P48K), have been reported by Gaillard et al [93; in the light of the now available sequence-specific assignments the observed 'H NMR spectral perturbations may be re-interpreted and reasonably accounted for on the basis of local and symmetrical rearrangements of the two clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Ferricyanide is used as a reagent to oxidize succinate dehydrogenase, which contains [2Fe-2S], [3Fe-4S] and [4Fe-4S] clusters [13]. Oxidation of Clostridium pasteurianum 8Fe Fd with ferricyanide was used to convert one or both of the [4Fe-4S] clusters to [3Fe-4S] clusters for spectroscopic characterization [14][15][16]. The same reaction can be carried out on the [4Fe-4S] clusters in mitochondrial aconitase (mAc) [17,18], Bacillus stearothermophilus Fd [19] and Desulfovibrio gigas FdII [20].…”
Section: Introductionmentioning
confidence: 99%
“…The selective oxidative degradation of [4Fe‐4S] clusters into the corresponding cubane [3Fe‐4S] clusters has been studied with several bacterial‐type ferredoxins from Azotobacter vinelandii, Clostridium pasteurianum , and Pyrococcus furiosus [1–7]with interest of chemistry of the biological iron‐sulfur (FeS) clusters. Unlike the cases of monocluster‐type ferredoxins, the intermediate products of 7Fe‐containing dicluster ferredoxins by oxidative degradation remain incompletely characterized.…”
Section: Introductionmentioning
confidence: 99%